The Reliability of Four Elements of Research in Effective Mitigation of Covid-19 Pandemic for Rapid Global Health and Economic Recovery with focus on Nigeria - AKPAN, E. Ebenezer, Ph.D, FCICN, AP, PPGDCA, PHDCDPM; Commy Precious GODDYMKPA, Ph.D (Research Parks Publishing LLC, 2020)
The study sought to examine the extent of the reliability of four elements of research in effective mitigation of Covid-19 pandemic for rapid global health and economic recovery. Ex-post facto research design was adopted for the study. The study was conducted in Nigeria. The population of the study comprised social researchers, psychologists, and medical researchers. Simple random sampling technique was used to select 50 Social researchers, 50 psychologists, and 50 medical researchers, giving a total of 150 respondents constituting the sample size for the study. The Main Instrument used in this study was a Questionnaire titled “Elements of Research and Effective Mitigation of Covid-19 Pandemic (EREMCPQ)”. Face validation of the instrument was carried out to ensure that the instrument has the accuracy, appropriateness, completeness and the language of the study under consideration. Cronbach Alpha technique was used to determine the level of reliability of the instrument. The reliability coefficient obtained was 0.84 and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical techniques such as simple regression. The test for significance was done at 0.05 alpha levels. The study concluded that there is significant joint influence of the four elements of research (objectivity, systematicity intellectuality and purposefulness in that order) on effective mitigation of Covid-19 pandemic for rapid global health and economic recovery. One of the recommendations was that It is pertinent that medical and social researchers need to prioritize the four elements of research when (objectivity, systematicity, intellectuality and purposefulness) if their quest for mitigation of covid-19 must be yield a useful result.